Mental health and post-traumatic stress disorder in firefighters: an integrated analysis from an action research study - Oliveira, Joana; Aires Dias, Joana; Duarte, Isabel Catarina; Caldeira, Salomé; Marques, António Reis; Rodrigues, Vítor; Redondo, João; Castelo-Branco, Miguel (Frontiers in Psychology, 2023)
Introduction The presence of post-traumatic stress disorder (PTSD) symptomatology in firefighters is an ever-pressing issue that requires close attention for adequate interventions. The present study investigated PTSD and global psychopathology prevalence in a sample of highly risk-exposed Portuguese firefighters, collected after the widespread deadly wildfires in 2017 that ravaged the country. Following an action research approach, the aim of this study was to depict this sample and examine the impact of cumulative adverse experiences on their mental health, which is a phenomenon worth attention. Method From an initial sample of 283 firefighters who manifested interest in participating, a total of 139 firefighters from the Coimbra District, of whom 130 unequivocally experienced a potentially traumatic/adverse event as a firefighter, completed BSI (to obtain indicators on psychopathology), QEPAT (an inventory of adverse events possibly experienced as a firefighter), and PCL-5 (a measure of PTSD symptomatology) through an online survey during the year 2018 by the Regional Medical Organization, as proposed and supervised by the local Centre for Prevention and Treatment of Psychological Trauma (CPTTP). Results We found a global prevalence of 8.6% of possible PTSD and 14.4% of possible psychopathology (n = 139). When considering only firefighters who unequivocally reported a potentially traumatic/adverse event as a firefighter (n = 130), 9.2% present possible PTSD, and 13.8% present possible global psychopathology. This sample experienced a mean of 28 adverse events during firefighting work. Linear regressions (n = 118) demonstrated that the perceived severity of the most traumatic event reported and the experience of more adverse events were both related to an increase in PTSD symptomatology. Global psychopathology was associated with PCL-5 scores, with an emphasis on paranoid ideation, hostility, depression, anxiety, and phobic anxiety. Discussion The severe wildfires of 2017 did not impact PTSD scores in this sample (collected the year after), suggesting that cumulative adverse events are more important than particular episodes. However, the number of reported events was related to PTSD scores. These results can be used to develop interventions that target all firefighters by addressing risk and protective factors. This action research study motivated specialized aid for firefighters involved in this study.